Martin Luther King, Jr : nonviolent strategies and tactics for social change - Ansbro, John J. (Lanham, Md. : Madison Books ; [United States] Distributed by National Book Network, 2000)
Examines his contribution as a philosopher and theologian to issues of racial and social justice and his drive to eradicate oppression through the doctrine of nonviolence.
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Philosophy. King, Martin Luther, -- Jr., -- 1929-1968. King, Martin Luther, -- (1929-1968)